Relación entre la deficiencia de hierro y el desempeño intelectual en niños de edad escolar - Otero, Gloria; Aguirre, Dalia; Porcayo, María del Rosario; Millán, Lucila; Colín, Miguel A.; Quiroz, Claudia (CIENCIA ergo-sum; Vol. 4 Núm. 3 (1997): CIENCIA ergo-sum (noviembre 1997-febrero 1998), 2017)
-